A survey on the physical activity involvement among Universiti Sains Malaysia Health Campus students - Wahab, Siti Nursyaima Abd (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
Recreational activity is an activity of leisure, which is usually done to reduce stress, amusement, pleasure, and good for health benefits. The main objective of this study is to determine participation in recreational activities among Universiti Sains Malaysia Health Campus (USMKK) students. In this cross-sectional study, 86 participants (N=86) were recruited with 29 male students and 57 female students. Participations in this study were on voluntarily basis. The data of this study were collected using a modified Global Physical Activity Questionnaire (GPAQ) questionnaire that was distributed via the online platform and was analysed using descriptive test of Statistical Package for Social Sciences (SPSS) version 26. The results showed, vigorous-intensity outdoor recreational activities, 38 participants (44.2%) did not involve while the other 48 (55.8%) participants did. Moderate-intensity outdoor recreational activities, 14 participants (16.3%) did not involve, 72 participants (83.7%) involved. Vigorous-intensity indoor recreational activities, 46 participants (53.5%) did not involve, 40 participants (46.5%) involved. Moderate-intensity indoor recreational activities, 31 participants (36.0%) did not involve, 55 participants (64.0%) involved. The time spends by USMKK students on physical activities also complies with the physical activity recommended by World Health Organization (WHO). In conclusion, most of the students participated in recreational activities either it was vigorous-intensity, moderate-intensity, indoor, or outdoor.